Flame-retardant polypropylene bead, preparation method thereof and molded part

By adding glass fiber/natural cellulose/titanium dioxide composite melt strength stabilization additive to the core layer of the EPP product, polypropylene foam beads with excellent flame retardant effect were prepared, which solved the problem that existing EPP products were difficult to meet the self-extinguishing requirements of off-fire, and achieved a combination of high density and excellent flame retardant performance.

CN119613801APending Publication Date: 2025-03-14WUXI HI TEC ENVIRONMENTAL MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411881851.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing EPP products are difficult to meet the flame retardant requirements of self-extinguishing of fire, especially on high-speed molded parts, where lower density leads to faster and more uncontrollable combustion.

Method used

Polypropylene foam beads with excellent flame retardant effects were prepared by adding glass fiber/natural cellulose/titanium dioxide composite melt strength stabilization additive to the core layer of the pre-foamed particles. The composition of the core layer includes polypropylene, glass fiber, natural cellulose, titanium dioxide and flame retardant, and is prepared by a supercritical carbon dioxide kettle foaming process.

Benefits of technology

The flame retardant performance and density of polypropylene foamed beads are improved, so that their molded parts can stably meet the flame retardant requirements of UL-94/V-0 grade, and at the same time, the stability and mechanical properties of the foam system are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure KXONA1GZUH8YNRDLJKFF0MGIXV6HFE4UESISICUR
    Figure KXONA1GZUH8YNRDLJKFF0MGIXV6HFE4UESISICUR
Patent Text Reader

Abstract

The invention relates to the technical field of functional foaming materials, in particular to flame-retardant polypropylene beads, a preparation method of the flame-retardant polypropylene beads and a molded part, and the flame-retardant polypropylene beads are prepared from pre-foamed particles through a kettle type foaming method; the pre-foamed particle comprises a core layer; the core layer comprises a melt strength enhancer and a flame retardant; the melt strength enhancer is prepared from the following raw materials in parts by weight: 50 to 60 parts of polypropylene P-1; 15 to 25 parts of glass fiber; 3-10 parts of natural cellulose; 10 to 30 parts of titanium dioxide; the flame retardant is a mixture composed of ammonium polyphosphate and pentaerythritol according to a mass ratio of 2: 1. According to the flame-retardant polypropylene foamed bead provided by the invention, the melt strength enhancer is introduced, so that the stability (strength and size) of a foam system is favorably improved, and the melt strength enhancer and the flame retardant are simultaneously introduced, so that the density of the bead is favorably improved, and a molded part of the bead can stably meet the flame-retardant requirement of self-extinguishing after being away from fire.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional foaming materials, in particular to flame-retardant polypropylene beads and a preparation method and a molded product thereof. Background Art

[0002] Expanded polypropylene beads (EPP for short) are a new type of environmentally friendly foam material that is both high-strength and lightweight. Its apparent density is controllable and can reach 10-250g / L according to production foaming control. It has a large application market in the fields of automobiles, packaging, furniture and home decoration, and new energy battery turnover. In recent years, with the expansion of the EPP market and the transformation of the original EPS market, the functional requirements for the use of EPP have gradually increased, and the application field has gradually expanded to high-end application scenarios such as aerospace and military industry. Conventional EPP products can no longer meet the increasingly high functional requirements, such as EPP conductive series, EPP flame retardant series, and EPP strength enhancement series.

[0003] Among them, the conventional EPP flame retardant series is divided into the automotive field, furniture field, aerospace field, etc. according to different usage scenarios. The flame retardant grades are divided into three levels: conventional, flame-retardant, and self-extinguishing. Among the requirements for self-extinguishing, the highest evaluation is the UL-94 V-0 grade standard, which not only has requirements for burning time and burning dripping, but also has corresponding requirements for the ignition length of the burning material. Only when the above three are met at the same time can it be evaluated as V-0 grade. Conventional EPP products, due to their unique foam structure, have a low melting heat. During the combustion process, it is difficult to achieve no dripping and a shorter burning and melting distance. Especially on EPP high-ratio moldings, the lower density leads to a longer burning distance, so it burns faster and is more uncontrollable, and it is difficult to meet the requirements of self-extinguishing. Summary of the invention

[0004] In order to solve the problem that EPP products in the prior art are difficult to meet the requirements of self-extinguishing when away from fire, the present invention provides a flame retardant polypropylene foam bead. The flame retardant polypropylene foam bead is prepared by adding a glass fiber / natural cellulose / titanium dioxide composite melt strength stabilizing additive to obtain polypropylene foam beads with excellent flame retardant effect, thereby solving the problem that EPP products in the prior art are difficult to meet the requirements of self-extinguishing when away from fire.

[0005] The technical solution adopted by the present invention to solve its technical problem is: A flame retardant polypropylene foamed bead is prepared from pre-foamed particles by a kettle foaming method; The pre-expanded particles include a core layer; The core layer includes a melt strength enhancer and a flame retardant; The raw materials of the melt strength enhancer include, by weight: Polypropylene P-1 50-60 parts; Glass fiber 15-25 parts; 3-10 parts of natural cellulose; 10-30 parts of titanium dioxide; The flame retardant is a mixture of ammonium polyphosphate and pentaerythritol in a mass ratio of 2:1.

[0006] Optionally, the melt strength enhancer is prepared according to the following method: S01: activating the glass fiber with an alkaline solution to obtain a pretreated glass fiber; S02: washing and drying the natural cellulose to obtain pretreated natural cellulose; S03: calcining and activating the titanium dioxide at high temperature, filtering and grinding the titanium dioxide to obtain pretreated titanium dioxide; S04: According to the formula, the pretreated glass fiber, the pretreated natural cellulose, and the pretreated titanium dioxide are blended and dispersed with the polypropylene P-1 through a high mixer, and then granulated through twin-screw extrusion to obtain the melt strength enhancer.

[0007] Optionally, the glass fiber has a length of 15-30 mm and a diameter of 5-15 μm.

[0008] Optionally, the natural cellulose has a length of 1-2 mm and a diameter of 20-30 μm.

[0009] Optionally, the titanium dioxide is rutile titanium dioxide with a particle size of 200-300 nm.

[0010] Optionally, the polypropylene P-1 is a random copolymer polypropylene with a melting point of 130-140° C. and a melt index of 20-40 g / 10 min.

[0011] Optionally, the raw materials of the core layer include the following components in parts by weight: Polypropylene P-2 100 parts; Nucleating agent 0.05-0.1 part; Lubricant 0.1-0.2 parts; 3-5 parts of the melt strength enhancer; Flame retardant 5-15 parts.

[0012] Optionally, the polypropylene P-2 has a melting point of 145-150° C. and a melt index of 6-9 g / 10 min.

[0013] Optionally, the nucleating agent is zinc borate.

[0014] Optionally, the lubricant is selected from at least one of erucamide and oleamide.

[0015] Optionally, the pre-expanded particles further include a skin layer coated on the outside of the core layer; the raw material of the skin layer is polypropylene P-3; the melting point of the polypropylene P-3 is 125-135° C., and the melting index is 10-15 g / 10 min.

[0016] Another object of the present invention is to provide a method for preparing the flame retardant polypropylene foam beads as described above, comprising the following steps: S1: blending the raw materials of the pre-foamed microparticles according to the formula amount, and then extruding and drawing the pre-foamed microparticles through a co-extrusion process to prepare the pre-foamed microparticles; S2: The flame-retardant pre-foamed microparticles are subjected to a supercritical carbon dioxide autoclave pressure foaming process to obtain flame-retardant polypropylene foamed beads.

[0017] Another object of the present invention is to provide a molded article, which is obtained by pre-pressing and molding the flame-retardant polypropylene foam beads as described above.

[0018] The beneficial effects of the present invention are: The flame-retardant polypropylene foam beads provided by the present invention not only help to improve the stability (strength and size) of the foam system by introducing a melt strength enhancer, but also help to increase the density of the beads by simultaneously introducing the melt strength enhancer and the flame retardant, so that the molded parts can stably meet the flame retardant requirements of self-extinguishing when away from the fire. DETAILED DESCRIPTION

[0019] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0020] In order to solve the problem that the EPP products in the prior art are difficult to meet the requirements of self-extinguishing after leaving the fire, the present invention provides a flame-retardant polypropylene foamed bead, which is prepared by a kettle foaming method from pre-foamed particles; wherein the pre-foamed particles include a core layer; the core layer includes a melt strength enhancer and a flame retardant; The raw materials of the melt strength enhancer include, by weight: Polypropylene P-1 50-60 parts; Glass fiber 15-25 parts; 3-10 parts of natural cellulose; 10-30 parts of titanium dioxide; The flame retardant is a mixture of ammonium polyphosphate and pentaerythritol in a mass ratio of 2:1.

[0021] The flame-retardant polypropylene foam beads provided by the present invention improve the flame-retardant performance of the polypropylene foam beads through the synergistic effect of a melt strength enhancer and a flame retardant system; specifically, the flame-retardant effect is achieved through the high-temperature carbonization of polyphosphate and pentaerythritol, and at the same time, the melting and dripping defects of the foam body are greatly reduced during continuous ignition through the synergistic effect of natural cellulose / glass fiber / titanium dioxide. The presence of natural cellulose and titanium dioxide has a certain binding effect on the polypropylene molecular chain, and the titanium dioxide can also improve the heat dissipation capacity of the melt, so that it can be quickly fixed; the addition of natural cellulose, as a medium, improves the dispersibility of glass fiber and titanium dioxide in the system, and the hydroxyl structure contained in the natural cellulose can reduce the heat energy generated by the combustion system through the dehydration effect with phosphate at high temperature, reduce the accumulation of heat in the combustion process, and play a certain role in reducing the droplets.

[0022] The flame-retardant polypropylene foam beads provided by the present invention not only help to improve the stability (strength and size) of the foam system by introducing a melt strength enhancer, but also help to increase the density of the beads by simultaneously introducing the melt strength enhancer and the flame retardant, so that the molded parts can stably meet the flame retardant requirements of self-extinguishing when away from the fire.

[0023] The preferred melt strength enhancer of the present invention is prepared according to the following method: S01: activating the glass fiber by an alkaline solution to obtain pretreated glass fiber; Specifically, the process can be as follows: put the selected glass fiber into an ethanol solution, stir it, wash off the impurities and grease on the surface, filter and dry it; use a 5% by mass sodium hydroxide solution to activate its surface, stir and soak it for 30 minutes, filter it, wash it with clean water to remove the alkaline solution on the surface, and dry it for use; S02: washing and drying the natural cellulose to obtain pretreated natural cellulose; The specific process is as follows: the selected natural cellulose is put into an ethanol solution for ultrasonic cleaning, and then dried for use; S03: calcining and activating the titanium dioxide at high temperature, filtering and grinding the titanium dioxide to obtain pretreated titanium dioxide; The specific process is as follows: the selected titanium dioxide is calcined at 1000°C for 30 minutes, filtered and ground, and cooled for later use; The present invention helps to remove impurities in the powder and improve the purity of the product by calcining the titanium dioxide at a high temperature. Compared with directly introducing uncalcined titanium dioxide, it helps to improve the dispersion performance of the product in the system during subsequent processing.

[0024] S04: According to the formula, pretreated glass fiber, pretreated natural cellulose, and pretreated titanium dioxide are blended and dispersed with polypropylene P-1 through a high mixer. In order to improve the uniformity of mixing, 2% liquid paraffin by weight of the raw materials can be added; after blending, granulation is performed through twin-screw extrusion, and the preferred pelletizing length is 2-3mm and the weight is 20-30mg. The pellets are dried for standby use to obtain a melt strength enhancer.

[0025] In step S04, in order to reduce the damage to the fiber structure during the mixing process, a short-stroke high-torque twin-screw extruder (preferably a 35-speed extruder) is selected with a processing temperature of 180-220°C.

[0026] In order to take into account both the stability and flame retardancy of the foam system, the present invention preferably has a glass fiber length of 15-30 mm and a diameter of 5-15 μm; preferably has a natural cellulose length of 1-2 mm and a diameter of 20-30 μm; preferably has a titanium dioxide of rutile type with a particle size of 200-300 nm; preferably has a polypropylene P-1 of random copolymer with a melting point of 130-140°C and a melt index of 20-40 g / 10 min (220°C, 2.15 kg), so as to improve the uniformity of fiber processing dispersion. If the melting point of polypropylene is too low or too high, it is not conducive to the uniformity of fiber dispersion during processing.

[0027] In order to ensure the flame retardant properties and mechanical properties of the flame retardant polypropylene foam beads, the present invention preferably comprises the following components in parts by weight: Polypropylene P-2 100 parts; Nucleating agent 0.05-0.1 part; Lubricant 0.1-0.2 parts; 3-5 parts of melt strength enhancer; Flame retardant 5-15 parts.

[0028] Among them, the melting point of polypropylene P-2 is 145-150°C, and the melt index is 6-9g / 10min (220°C, 2.15kg), so as to utilize the appropriate flow rate and crystallinity of polypropylene within the melt index range, take into account the molding pressure and comprehensive strength, and improve the uniformity of mixing in extrusion blending.

[0029] In the present invention, the preferred nucleating agent is zinc borate, and further preferably the particle size is 5-10 μm; the preferred lubricant is at least one selected from erucamide and oleamide.

[0030] The pre-expanded microparticles provided by the present invention also include a skin layer coated on the outside of the core layer, and the mass ratio of the skin layer to the core layer is preferably (2-8):100, that is, the mass of the skin layer is (2-8)% of the mass of the core layer; the raw material of the skin layer is polypropylene P-3; preferably, the melting point of polypropylene P-3 is 125-135°C, and the melt index is 10-15g / 10min (220°C, 2.15kg), so that by selecting a polypropylene with a lower melting point as the skin layer, it is helpful to effectively reduce the molding pressure during molding; at the same time, a higher melt index can improve the integrity of the coating during the skin layer coating, which is helpful for the stability of the pull rod.

[0031] Another object of the present invention is to provide a method for preparing the flame retardant polypropylene foam beads as described above, the preparation method comprising the following steps: S1: After blending the raw materials of the pre-foamed microparticles according to the formula amount, the pre-foamed microparticles are extruded and drawn by a co-extrusion process to prepare pre-foamed microparticles with a length of 1.5-2.5 mm and a weight of 0.5-1.0 mg; Preferably, a single screw is used for dispersion and mixing in this step, and the extrusion temperature is preferably 210-230°C; S2: subjecting the flame-retardant pre-foamed particles to a supercritical carbon dioxide autoclave pressure foaming process to obtain a flame-retardant pre-foamed particle; in this step, the foaming may be primary or secondary; the specific process of the secondary foaming is to foam a flame-retardant foamed particle primary product through a supercritical carbon dioxide autoclave pressure foaming process, preferably with a primary product density of 40-100 g / L; subjecting the flame-retardant foamed particle primary product to a secondary foaming process to obtain a flame-retardant foamed particle secondary product with a lighter density (density 20-40 g / L), namely, flame-retardant polypropylene foam beads; Preferably, in this step, the foaming temperature of the primary product is 148-152°C and the foaming pressure is 1.5-2.6MPa; the secondary product needs to be cured at room temperature for 12 hours, pressurized with compressed air (pressurization pressure 0.4-0.6MPa, time 8-12h), and then foamed again through EPP secondary foaming equipment.

[0032] The preparation method of the flame-retardant polypropylene foam beads provided by the present invention not only helps to improve the stability (strength and size) of the foam system by introducing a melt strength enhancer, but also helps to increase the density of the beads by simultaneously introducing the melt strength enhancer and the flame retardant, so that the molded parts can stably meet the flame retardant requirements of self-extinguishing when away from the fire.

[0033] Another object of the present invention is to provide a molded part, which is obtained by pre-pressing and molding the flame-retardant polypropylene foam beads as described above, and then drying and cooling to shape; preferably, after pre-pressing with compressed air, steam molding is carried out through an EPP molding machine, and the part is baked and shaped at 80°C to obtain the desired flame-retardant foamed polypropylene molded part, that is, a molded part.

[0034] The scheme provided by the present invention provides a light-colored highly flame-retardant polypropylene foam particle and a molded product thereof. By adding a glass fiber / natural cellulose / titanium dioxide composite melt strength stabilizing agent, polypropylene foam beads with excellent flame retardant effect can be obtained, and the bead density can be as low as 30g / L. The molded products thereof, in particular, by adding a melt strength stabilizer, also have a certain improvement effect on the stability (strength and size) of the foam system.

[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.

[0036] Unless otherwise specified, the melt strength enhancer in each embodiment of the present invention and the comparative example is prepared according to the following method: S01: Pretreatment of glass fiber: Put the selected glass fiber (length 15-30 mm, diameter 5-15 μm) into an ethanol solution and stir to clean the impurities and grease on the surface. After filtering and drying, the surface is activated with a 5% by mass sodium hydroxide solution. After stirring and soaking for 30 minutes, the surface is filtered and washed with clean water to remove the alkaline solution on the surface, and then dried for use; S02: Pretreatment of natural cellulose: The selected natural cellulose (1-2 mm, diameter 20-30 μm) is ultrasonically cleaned in an ethanol solution and then dried for later use; S03: Activation of titanium dioxide: calcine the selected rutile titanium dioxide (particle size 200-300nm) at 1000℃ for 30min, filter and grind, cool and set aside; Step 4: Preparation of melt strength enhancer: According to the weight proportions, 20 parts of the pretreated glass fiber, 5 parts of natural cellulose and 20 parts of titanium dioxide are blended and dispersed with 55 parts of polypropylene P-1 (melting point of 135°C, melt index of 30g / 10min (220°C, 2.15kg)) and 0.2 parts of liquid paraffin by a high mixer, and then granulated by twin-screw extruder (short-stroke high-torque twin-screw 35 machine, processing temperature of 200°C). The pellets are cut into 2.5mm in length and weigh 25mg. The pellets are dried for later use to obtain a melt strength enhancer, recorded as S-1.

[0037] The difference between the preparation process of the melt strength enhancer S-2 in the comparative example of the present invention and the preparation process of S-1 is that the glass fiber is not activated by alkali solution.

[0038] The difference between the preparation process of the melt strength enhancer S-3 in the comparative example of the present invention and the preparation process of S-1 is that no natural cellulose is added.

[0039] The difference between the preparation process of the melt strength enhancer S-4 in the comparative example of the present invention and the preparation process of S-1 is that no titanium dioxide is added.

[0040] The difference between the preparation process of the melt strength enhancer S-5 in the comparative example of the present invention and the preparation process of S-1 is that the titanium dioxide is not calcined.

[0041] The melting point of polypropylene P-2 in the following embodiments and comparative examples is 145°C, and the melt index is 7 g / 10 min (220°C, 2.15 kg); the melting point of polypropylene P-3 is 125°C, and the melt index is 15 g / 10 min (220°C, 2.15 kg); the nucleating agent is zinc borate with a particle size of 8 μm; the lubricant is erucamide; the flame retardant-1 is a mixture of ammonium polyphosphate and pentaerythritol in a mass ratio of 2:1; and the flame retardant-2 is a decabromodiphenyl ether spectral halogen-containing flame retardant.

[0042] The test method in the present invention is as follows: 10% compression strength: According to GB / T8813-Determination of Compression Properties of Rigid Foam Plastics, a sample with a size of 100*100*50mm was subjected to compression test using a universal tensile testing machine. The compression rate was 5mm / min, and the compression strength was taken when the deformation was 10%. Five groups of samples were tested cumulatively and the average value was taken. The test results are shown in Table 1.

[0043] The formulations and process parameters of each embodiment and comparative example are shown in Table 1: Table 1 It can be seen from the data in the above table that the molded parts provided by the embodiments of the present invention all have excellent mechanical properties and can stably meet the flame retardant requirements of UL-94 / V-0.

[0044] All comparative examples in the present invention are compared with Example D. As can be seen from Table 1, the melt strength enhancer provided by the present invention works synergistically with the specific flame retardant to improve the stability of the molded parts while imparting them with excellent flame retardant properties.

[0045] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A flame retardant polypropylene foamed beads, characterized in that: It is prepared from pre-foamed microparticles by a kettle foaming method; The pre-expanded particles include a core layer; The core layer includes a melt strength enhancer and a flame retardant; The raw materials of the melt strength enhancer include, by weight: Polypropylene P-1 50-60 parts; Glass fiber 15-25 parts; 3-10 parts of natural cellulose; 10-30 parts of titanium dioxide; The flame retardant is a mixture of ammonium polyphosphate and pentaerythritol in a mass ratio of 2:

1.

2. The flame retardant polypropylene foam beads according to claim 1, characterized in that: The melt strength enhancer is prepared as follows: S01: activating the glass fiber with an alkaline solution to obtain pretreated glass fiber; S02: washing and drying the natural cellulose to obtain pretreated natural cellulose; S03: calcining and activating the titanium dioxide at high temperature, filtering and grinding the titanium dioxide to obtain pretreated titanium dioxide; S04: According to the formula, the pretreated glass fiber, the pretreated natural cellulose, and the pretreated titanium dioxide are blended and dispersed with the polypropylene P-1 through a high mixer, and then granulated through twin-screw extrusion to obtain the melt strength enhancer.

3. The flame retardant polypropylene foam beads according to claim 1, characterized in that: The glass fiber has a length of 15-30 mm and a diameter of 5-15 μm.

4. The flame retardant polypropylene foam beads according to claim 1, characterized in that: The natural cellulose has a length of 1-2 mm and a diameter of 20-30 μm.

5. The flame retardant polypropylene foam beads according to claim 1, characterized in that: The titanium dioxide is rutile titanium dioxide with a particle size of 200-300nm.

6. The flame retardant polypropylene foam beads according to claim 1, characterized in that: The polypropylene P-1 is a random copolymer polypropylene with a melting point of 130-140° C. and a melt index of 20-40 g / 10 min.

7. The flame retardant polypropylene foam beads according to any one of claims 1 to 6, characterized in that: The raw materials of the core layer include the following components in parts by weight: Polypropylene P-2 100 parts; Nucleating agent 0.05-0.1 part; Lubricant 0.1-0.2 parts; 3-5 parts of the melt strength enhancer; Flame retardant 5-15 parts.

8. The flame retardant polypropylene foam beads according to claim 7, characterized in that: The polypropylene P-2 has a melting point of 145-150° C. and a melt index of 6-9 g / 10 min.

9. The flame retardant polypropylene foam beads according to claim 7, characterized in that: The nucleating agent is zinc borate.

10. The flame retardant polypropylene foam beads according to claim 7, characterized in that: The lubricant is selected from at least one of erucamide and oleamide.

11. The flame retardant polypropylene foam beads according to claim 7, characterized in that: The pre-foamed particles also include a skin layer coated on the outside of the core layer; the raw material of the skin layer is polypropylene P-3; the melting point of the polypropylene P-3 is 125-135° C., and the melting index is 10-15 g / 10 min.

12. A method for preparing the flame retardant polypropylene foam beads according to any one of claims 1 to 11, characterized in that: The steps include: S1: blending the raw materials of the pre-foamed microparticles according to the formula amount, and then extruding and drawing the pre-foamed microparticles through a co-extrusion process to prepare the pre-foamed microparticles; S2: The flame-retardant pre-foamed microparticles are subjected to a supercritical carbon dioxide autoclave pressure foaming process to obtain flame-retardant polypropylene foamed beads.

13. A molded article, characterized in that: The flame retardant polypropylene foam beads are obtained by pre-pressing and molding as described in any one of claims 1 to 11.

Citation Information

Cited By

  • Intelligent response type flame-retardant polypropylene foamed bead as well as preparation method and application thereof

    CN122167811A